Development of an engine control unit for the argo vanguard 2 - Devasahayam Martin (2008)
This dissertation presents the design and development of a microcontroller based accelerator (MCBAS) and choke systems (MCBCS) for an ARGO vanguard 2 (6*6). The proper mechatronics system development was performed to attain the two systems. The mechanical design, electronic circuit development and software development of both systems are described with sufficient details and the problem faced in every section is discussed.